Extreme weekly locoregional hypofractionated radiation in elderly women with non-metastatic breast cancer. (September 2021) - Rais, Fadoua; Tsui, James Man Git; Daianska, Alyssa; Faye, Mame Daro; Lambert, Christine; David, Marc; Panet-Raymond, Valerie; Azoulay, Melissa; Saidi, Asma; Hijal, Tarek
Highlights: Extreme hypofractionated radiation is a regimen delivering >5 Gy/fraction. It is a safe alternative to normofractionation in locoregional radiation setting. It confers excellent oncologic outcomes in term of locoregional control and survival. Abstract: Background and purpose: Breast cancer locoregional (LR) radiation in the elderly requires careful consideration between the benefits of aggressive treatment and its potential toll on these patients. Extreme weekly LR hypofractionated radiation (HFRT), delivering >5 Gy per fraction, may be better suited in such a population. It represents a good compromise between RT omission and exhaustive daily radiation. This study aims to report the local and LR control rate as well as the acute and long-term side effects of the elderly patients treated with HFRT in our institution, and to compare these results to those from the literature. Materials and methods: We conducted a retrospective study by reviewing medical records of elderly patients with breast cancer treated with adjuvant once-weekly LR HFRT between 2011 and 2020. Fifty patients presenting with primary non-metastatic node-positive breast tumors were included. Treatment outcomes including local/LR control and overall survival were reported. Early and late toxicity profiles were also assessed. Results: After a median follow-up of 4.8 years, only one local recurrence in the chest wall occurred and there was no regional recurrence. The distant metastatic rate was 6%. The long-term recurrence-free survival rate was 80% at 5 years. The cause specific survival rate was 90% at 5 years. The overall survival rate was 69.4% and 55.5% at 3 and 5 years, respectively. There were 44 (88%) patients with Grade 1 or 2 early toxicity. There was no Grade 3 or higher acute toxicity registered. Late toxicity was mainly Grade 1 or 2 subcutaneous fibrosis, lymphoedema, and neuropathy except for one patient with Grade 3 fibrosis. Conclusion: Extreme LR HFRT is well tolerated with good outcomes and is a good alternative for elderly and frail patients. Our results confirm the efficacy and safety of such a regimen. Further randomized trials assessing both oncologic outcome and toxicity profile are justified.